Network layer communication protocol design for underwater agriculture farming. (17th January 2022) - Manikandan, T. T.; Sukumaran, Rajeev; Radhakrishnan, M.; Christhuraj, M. R.; Saravanan, M.
Summary: In recent times, underwater agriculture farming is seen as a viable alternative to land‐based farming by agricultural scientists due to increasing limitations in land‐based farming areas around the world. But farming underwater is not as easy as it is said. Continuous monitoring of different parameters of the water inside the biosphere where the herbs, crops, and plants are cultivated is one of the highest priorities for the effective outcome in underwater farming. To achieve such precise monitoring, sensor‐based data collection from the underwater biosphere is the only way. Employing human divers for monitoring of water parameters has many limitations such as diving time, accidents due to harsh underwater environment. Alternatively, adopting sensor‐based monitoring provides spatial and temporal flexibility. But one of the significant challenges of such an underwater wireless sensor network (UWSN) is ensuring reliable communication between the underwater sensors and surface station. To ensure reliable delivery of sensed information network layer operation is vital. The underwater environment has unique challenges such as high interference, harsh environment, limited lifetime, and short network lifetime the network layer protocols of terrestrial networks can't be adopted into the underwater environment. So this research focuses on the development of a mathematical model for network layer communication using stochastic network calculus (SNC) taking into consideration the requirements of underwater agriculture farming application. In this research, the delay and backlog bounds of the proposed model are derived. The proposed mathematical model is also evaluated for its correctness using the discrete event simulation. Abstract : Underwater Agriculture Farming demands precise monitoring of the key parameters of waters such as water temperature, internal oxygen, internal carbon dioxide, and internal humidity in the biospheres where the herbs and plants are farmed. So, this research focuses on the modelling of network layer design for UWSN based on Depth Based Routing using SNC. The delay and backlog bound of the proposed model is analytically derived using SNC and the model has been evaluated using discrete event simulations.